POLITICAL-CRIMINAL NEXUS (Annual of the Faculty of Philosophy in Skopje, 2011)
A political-criminal nexus, the concentration and fusion of political and criminal power, is increasingly reaching the highest level of many nation-states. Organized crime groups develop collaborative relationships with state authorities to gain access to, and to exploit for their own purposes, the political Economical and social apparatus of the state. To increase the security of their operations, they also try to develop arrangements with local and/or national, political and legal authorities. For their part, state authorities seek cooperative relationships with criminal elements for various reasons such as personal benefits, securing votes, money, or to control enemies.The study seeks to identify the factors that facilitate the entrenchment of the political-criminal nexus, such as rapid technological change, privatization or political transition.The objectives of this paper are to determine with precision how this relationships are established, what collaborative activities are undertaken by this nexus, and to identify the methods of disrupting this ties.
Keywords: POLITICAL-CRIMINAL NEXUS; POWER; SECURITY; ORGANIZED CRIME; CORRUPTION